The role of AGG interruptions in the transcription of FMR1 premutation alleles. - Carolyn M Yrigollen; Federica Tassone; Blythe Durbin-Johnson; Flora Tassone (PLoS ONE, 2011)
Fragile X associated disorders are caused by a premutation allele in the fragile X mental retardation 1 gene (FMR1) and are hypothesized to result from the toxic effect of elevated levels of expanded FMR1 transcripts. Increased levels of FMR1 mRNA have indeed been reported in premutation carriers; however the mechanism by which expanded alleles lead to elevated levels of FMR1 mRNA in premutation carriers is unknown. Within the CGG repeat tract AGG interruptions are found, generally 1-3 present in normal/intermediate alleles (6-54 CGG repeats) and usually 0-1 in premutation alleles (55-200 CGG repeats). They are present at specific locations, generally occurring after 9 or 10 uninterrupted CGG repeats [(CGG)(9)AGG(CGG)(9)AGG(CGG)(n)]. We evaluated both the number of AGG interruptions and the resulting length of the uninterrupted 3' CGG repeat pure tract in premutation alleles derived from two large cohorts of male and female carriers to determine whether the presence of AGG interruptions or the length of a pure stretch of CGG repeats influence the levels of FMR1 mRNA in blood. Our findings indicate that neither the number of AGG interruptions, nor their position along the CGG tract have a significant affect on mRNA levels in premutation carriers. We also, as expected based on previous findings, observed a highly significant correlation between CGG repeat number (as both total length and length of pure CGG stretch) and FMR1 mRNA expression levels, in both males and females. Importantly, we did not observe any significant difference in FMR1 mRNA levels in premutation carriers based on age.